Secure multipath routing for multimedia communication in cognitive radio networks. (2018) - Bhattacharya, Ansuman; Ghosh, Sasthi C.; Sinha, Koushik; Sinha, Bhabani P.
In this paper, a novel technique for secure multihop communication in cognitive radio networks is proposed which allows the use of non-contiguous channels for communication of multimedia data without compromising the desired QoS. This technique first creates a number of sub-packets formed by suitably shuffling the bits of the original packet, finds multiple routes by executing the max-flow algorithm on a derivative of the network graph to meet the required bandwidth, suitably allocates channels for each hop in the multiple paths using the features of cognitive radio networks, and sends the sub-packets along these channels which are received by the destination node to form the original packet. This strategy also leads to significantly enhanced security of the data packets against the eavesdropping attack when multiple node-disjoint paths are chosen for transmitting the sub-packets.